Sunflower and climate changes: adaptation and mitigation potential from case study in RN Macedonia - Dimov, Zoran; Cukaliev, Ordan; Mukaetov Dusko; Tanaskovic Vjekoslav (Proceedings of the 20th International sunflower conference, 2022)
The negative effect of climate change on agriculture in the Republic of North Macedonia is increasing. The agricultural as whole and particular small farmers are expected to be exposed to prolonged heat waves, more severe droughts and floods. Less than 10% of agricultural land is irrigated, and with the exception of some parts of the country, water deficiency occurs in the summer, resulting in significant moister stress for summer and annual crop. For assessing the sunflower vulnerabilities in the south-east region in country to climate change and measuring the impacts of the proposed adaptation measures, the CropSyst model was used which offer to evaluate a set of adaptation options such changes in sowing date and irrigation management as adaptation strategies to forecast climate change. The time horizons that are studied are 2025 and 2050, and the comparison is done against a baseline year – 2000, considered as a representative of current conditions. The base scenario (SC 0) which was used as a referent one to which comparisons were made is without irrigation. Agro-management adaptations predicted 8 scenarios (SC1 – SC 8), with implementation of 3 types of irrigation: sprinkler, drip irrigation and furrow, with irrigation volume of 50 and 70 mm and number of irrigation ranked from min. 2 to max. 12 as well as every 20 days, depends from type of irrigation. The data from 2025 show that the average sunflower yield for all eight scenarios is higher for 38% compared with base scenario. By 2050 it’s predicted that average sunflower yield will decreased by approximately 17% compared with 2025, although the irrigation increased the yield in average for 17% in all scenarios compared with base one when 2050 is analyzed separately. Irrigation with sprinklers 4 times with irrigation application of 50 mm between 159 and 217 day of the year gave the highest yield of around 2200 kg ha-1 (SC 1), separating the sprinkler as more acceptable because with the same amount of water the yield was higher compared with furrow irrigation.
Keywords: climate changes, sunflower, adaptive measures, irrigation